2000
DOI: 10.2118/00-01-03
|View full text |Cite
|
Sign up to set email alerts
|

Counter-current Aspect of the SAGD Process

Abstract: The uniqueness of the steam assisted gravity drainage (SAGD) recovery process lies in the salient role of moving condensing boundaries and counter-current flows. Process effectiveness depends on the balance between rising steam and draining oil-condensate emulsions. Reservoir permeability, well completion and effective drainage-pumping of oil-condensate emulsions can affect such balance. A new, non-steady state, laboratory steam-front dynamic tracking technique was used in measuring steam-liquid counter-curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…The production well is operated at a maximum steam rate of 5 m 3 /day in order to prevent extensive steam loss. To initialize SAGD, a start-up procedure is simulated for heating up both the injection and production wellbores to ensure a high steam quality at the sand surface (Nasr et al, 2000).For the ES-SAGD case, C6 is injected into the reservoir as a surrogate of solvent with steam (Li and Mamora, 2011;Mohebati et al, 2010), with other parameters the same as the SAGD case. The k-values of C6 at different pressures and temperatures, provided by STARS User's Manual (2011), are used in the simulation.…”
Section: Casesmentioning
confidence: 99%
“…The production well is operated at a maximum steam rate of 5 m 3 /day in order to prevent extensive steam loss. To initialize SAGD, a start-up procedure is simulated for heating up both the injection and production wellbores to ensure a high steam quality at the sand surface (Nasr et al, 2000).For the ES-SAGD case, C6 is injected into the reservoir as a surrogate of solvent with steam (Li and Mamora, 2011;Mohebati et al, 2010), with other parameters the same as the SAGD case. The k-values of C6 at different pressures and temperatures, provided by STARS User's Manual (2011), are used in the simulation.…”
Section: Casesmentioning
confidence: 99%
“…On the basis of experimental results presented in the literature (Lelièvre, 1966;Bourbiaux and Kalaydjian, 1990;Kalaydjian, 1990;Nasr et al, 2000), it appears that mobilities determined in a countercurrent experiment are less than those determined for the same sand-fluid system, in a cocurrent experiment. Hence, it can be inferred that (Bentsen, 1998b):…”
Section: Derivation Of Basic Equationsmentioning
confidence: 85%
“…According to this process, heated oil around the steam fingers drains the counter-current flow against their steam. Nasr et al (2000) took a test for measuring steam-liquid counter-currents and co-current flows using a new non-steady state, laboratory steam-front dynamic tracking technique, and simulated the process using STARS software from the CMG group. The study concluded that for a given permeability, the counter-current steam front propagation rate is a linear function of time.…”
Section: Steam-fingering Theorymentioning
confidence: 99%